Interannual Variation in Offshore Advection of Amazon‐Orinoco Plume Waters: Observations, Forcing Mechanisms, and Impacts. Issue 11 (21st November 2017) - Fournier, S.; Vandemark, D.; Gaultier, L.; Lee, T.; Jonsson, B.; Gierach, M. M.
Abstract: This study investigates sea surface salinity (SSS) and sea surface temperature (SST) variations in the tropical Atlantic east of the Lesser Antilles, a region where freshwater advection from the Amazon and Orinoco Rivers, may potentially impact air‐sea interaction. Observations are used to document later‐summer variability and evaluate offshore riverine transport from 2010 to 2014. During this period, the largest difference in plume‐affected areas, defined as the extent covered by SSS lower than 35.5 pss, is found between 2011 and 2014. Plume waters covered 92% of the study region in 2011 and 60% in 2014, with the average SSS in the study region being 2 pss lower in 2011. Lagrangian particle tracking based on satellite‐derived ocean currents is used to diagnose the impact of the river plumes on SSS and SST from 2010 to 2014. Northward freshwater flux in summer 2014 was significantly weaker than fluxes in 2010–2013. This difference is not due to interannual discharge variability, but to significant changes in eddy‐driven transport and cross‐shore winds. In particular, the stronger cross‐shore wind in May 2014 restricted offshore freshwater flow and lead to a smaller plume‐affected area. Persistent SST gradients are often found near the plume edge, which may have implications for ocean‐atmosphere coupling associated with atmospheric convection. SST in the study region was 1°C higher in 2010 compared to other years, and is related to basin‐scale ocean‐atmosphere processes. Interannual variation in Amazon advective pathways and the associated SSS changes are also influenced by changes in the ITCZ position between 2011 and 2014. Key Points: NWTA distal river plume areal coverage shows marked spatial variability from 2010 to 2014, with 32% differences observed between 2011 and 2014 Persistent zonal SST gradients are linked to freshwater‐controlled surface salinity and show same interannual variability in cyclone season Eddy‐driven transport and cross‐shore wind play an important role in the advection of freshwater originating from the Amazon‐Orinoco Rivers